2015
DOI: 10.1177/0020764015577844
|View full text |Cite
|
Sign up to set email alerts
|

The humanistic and economic burden of providing care for a patient with schizophrenia

Abstract: Results indicate that caregivers of those with Schizophrenia experience a heightened humanistic and economic burden, especially relative to the burden experienced by non-caregivers. The fact that Schizophrenia not only affects the individual but also those who care for that individual is underscored by these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Caregivers of PWEs missed approximately 5 hours weekly due to absenteeism and 13 hours due to presenteeism, resulting in a mean annual cost of $26 188 (± $29 385) and median $17 788 ($3582‐$38 462). For the non‐caregiving population, indirect costs related to absenteeism and presenteeism were significantly lower and estimated to be $5015 ( P < .001) based on a published estimate from 2015 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Caregivers of PWEs missed approximately 5 hours weekly due to absenteeism and 13 hours due to presenteeism, resulting in a mean annual cost of $26 188 (± $29 385) and median $17 788 ($3582‐$38 462). For the non‐caregiving population, indirect costs related to absenteeism and presenteeism were significantly lower and estimated to be $5015 ( P < .001) based on a published estimate from 2015 …”
Section: Resultsmentioning
confidence: 99%
“…To identify such a group, we explored other analyses that estimated productivity losses for caregivers and included a comparator group of noncaregivers of approximately the same age as epilepsy caregivers. Although no other analyses estimated the impact of epilepsy caregiving, we did find a study that estimated absenteeism and presenteeism in caregivers of schizophrenia patients . Because patients with schizophrenia are more similar in age to PWEs than those with other conditions who had available data, we selected that study for inclusion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although severe, the course following a first episode of psychosis is rather heterogeneous and outcomes may vary from full recovery to a deteriorating chronic course [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. It has been observed that between two and five years after the first episode, psychotic disorders seem to plateau and follow a more stable course [41], so that a fair prediction of course can be made by year three [42].…”
Section: Relatives Of Patients With Psychosis Are Likelymentioning
confidence: 99%